1996
DOI: 10.1002/(sici)1097-4547(19960301)43:5<565::aid-jnr6>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

CaM I mRNA is localized to apical dendrites during postnatal development of neurons in the rat brain

Abstract: In the rat, a single calmodulin (CaM) protein is encoded by three separate genes which produce five different transcripts. The significance of the multiple CaM genes is not known; however, individual CaM transcripts could be targeted to specific intracellular sites. In this report, the cellular distribution of CaM I mRNAs was analyzed in the postnatal rat brain. The 4.0‐kb CaM I transcript was present in neuronal cell bodies and also localized to apical dendritic processes. In cerebral cortical neurons, the 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 67 publications
3
16
0
Order By: Relevance
“…Ribosomal proteins represent a large fraction of the total protein mass of a cell, and their shear amount may explain their presence among the isolated proteins. An alternative explanation is provided by the existence of dendritic mRNA in cerebellar Purkinje cells, such as mRNA for calmodulin (41), inositol 1,4,5-trisphosphate receptor type 1 (42), and L7 (43). We conclude that the purified ribosomal proteins may be part of the dendritic translational machinery in the Purkinje cells, leading to their enclosure into the forming PM vesicles during tissue homogenization.…”
Section: Discussionmentioning
confidence: 90%
“…Ribosomal proteins represent a large fraction of the total protein mass of a cell, and their shear amount may explain their presence among the isolated proteins. An alternative explanation is provided by the existence of dendritic mRNA in cerebellar Purkinje cells, such as mRNA for calmodulin (41), inositol 1,4,5-trisphosphate receptor type 1 (42), and L7 (43). We conclude that the purified ribosomal proteins may be part of the dendritic translational machinery in the Purkinje cells, leading to their enclosure into the forming PM vesicles during tissue homogenization.…”
Section: Discussionmentioning
confidence: 90%
“…There is evidence that newly synthesized mRNAs are preferentially transported to the postsynaptic zones of newly formed (Schacher et al, 1999) or recently activated synapses (Steward et al, 1998;Steward and Worley, 2001) or in the developing nervous tissue (Berry and Brown, 1996). In harmony with our previous results (Palfi et al, 1999), we established that the mRNAs corresponding to the three CaM genes are differentially targeted to the dendrites as the CaM I and CaM III mRNAs were more abundant than the CaM II transcript in this compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts of the CaM I and II genes were found within neurite extensions, whereas the CaM III mRNAs predominated in the cell body. Berry and Brown (1996) detected a transient distribution of the 4.0 kb CaM I mRNA in the apical dendrites of pyramidal and Purkinje neurons during postnatal days 5-20 in the rat. Later, Palfi et al (1999) demonstrated that the CaM mRNAs are significantly more abundant in the molecular layers (areas consisting mainly of dendrites) than in the white matter areas (containing mostly axonal tracts) in the adult rat brain.…”
Section: Introductionmentioning
confidence: 99%
“…The dendritic localization of some mRNAs may be developmentally regulated. For example, the mRNA for calmodulin can be detected by in situ hybridization in dendritic laminae of developing, but not mature animals (Berry & Brown 1996). This is consistent with the idea that local dendritic protein synthesis is especially important during periods of synaptogenesis (Palacios-Pru et al 1981Steward & Falk 1986).…”
Section: Mrnas In Dendrites In Vivomentioning
confidence: 97%